2018
DOI: 10.1346/ccmn.2017.064085
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of 2:1 Clay Minerals in a Kaolinite-Dominated Ultisol under Changing Land-Use Regimes

Abstract: Chemical denudation and chemical weathering rates vary under climatic, bedrock, biotic, and topographic conditions. Constraints for landscape evolution models must consider changes in these factors on human and geologic time scales. Changes in nutrient dynamics, related to the storage and exchange of K+ in clay minerals as a response to land use change, can affect the rates of chemical weathering and denudation. Incorporation of these changes in landscape evolution models can add insight into how land use chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Fungi promote soil aggregation and structural development by embedding grains into their hyphal network, and by forming secondary minerals that precipitate, in part, from the release of base cations (e.g., K + , Mg 2+ , Ca 2+ ) during mineral weathering 23 . Biominerals formed by free-living and symbiotic fungi (e.g., mycorrhizae) include aggregated iron hydroxides, calcium and magnesium oxalates, among others 53,57 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi promote soil aggregation and structural development by embedding grains into their hyphal network, and by forming secondary minerals that precipitate, in part, from the release of base cations (e.g., K + , Mg 2+ , Ca 2+ ) during mineral weathering 23 . Biominerals formed by free-living and symbiotic fungi (e.g., mycorrhizae) include aggregated iron hydroxides, calcium and magnesium oxalates, among others 53,57 .…”
Section: Resultsmentioning
confidence: 99%
“…Unresolved questions pertaining to mineral transformation mechanisms involve assessing relative controls of biochemical versus biomechanical weathering, indirect or direct microbe-mineral interactions, and whether microbes enhance or slow mineral dissolution 17,18 . Microscopy studies have examined biomechanical and biochemical weathering mechanisms that: weaken mineral structures through the fungal-driven oxidation of Fe(II) in biotite 19 , induce secondary mineral formation and biomineralization 20 , enhance microbial growth around nutrient-rich zones 21 , incongruently leach major and trace elements 10,22 , and exert control of K nutrient uptake and related clay mineral modifications under changing land-use regimes 23 . Atomic force microscopy has been used to detect the simultaneous occurrence of indirect and direct biochemical weathering, where it was observed that abundant small etching pits formed on mineral surfaces exposed to siderophores (molecular Fe chelators) released to solution by microbes, whereas fewer yet larger “biopits” formed on surfaces colonized directly by bacteria 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Soil pH (1:2 ratio of soil: water) was 6.2. XRD analysis revealed that the clay mineralogy of this soil is dominated by kaolinite and illite 78 .…”
Section: Methodsmentioning
confidence: 93%
“…In fact, the variation in these processes during ecosystem development can affect mineral weathering rates in shallow soils (e.g., Lawrence, Harden, & Maher, ,Lawrence, Steefel, & Maher, ). Recent work by Austin et al () shows that the translocation of K at depth to the surface by vegetation in a highly weathered, temperate forested ecosystem leads to the formation of 2:1 clays such as illite preferentially over 1:1 clays such as kaolinite, while work in rain forests have shown that cycling of Si by vegetation helps maintain kaolinite in the topsoil (Lucas, ; Lucas et al, ). Another phenomenon that is not included in our modeling is the effect of light molecular weight organic acids in promoting chemical weathering at shallow depths while inhibiting primary mineral weathering and increasing secondary mineral precipitation at greater depths (Lawrence, Harden, & Maher, ; Lawrence et al, ).…”
Section: Discussionmentioning
confidence: 99%